Parental Unemployment and Child Health in China - Janneke Pieters; Samantha Rawlings (Institute for the Study of Labor (IZA), 2016)
This paper studies the causal effect of maternal and paternal unemployment on child health in China, analyzing panel data for the period 1997-2004, when the country underwent economic reforms leading to massive layoffs. We find that paternal unemployment reduces child health, while maternal unemployment has beneficial child health impacts. Analysis of channels shows that paternal and maternal unemployment have different effects on income, time use, mothers' blood pressure, and certain health investments, including children's diets. Our results support the notion that traditional gender roles can explain why mothers and fathers' unemployment affect child health so differently.
Keywords: I12; J13; J69; O15; 330; child health; unemployment; nutrition; China